O07.5 The index case's partnership status is important in predicting the likelihood of persistence of introduced XDR NG among MSM. (14th July 2019) - Hui, Ben; Wood, James; Duan, Qibin; Regan, David
Abstract : Background: Extensively drug resistant (XDR) Neisseria gonorrhoeae (NG) strains have recently been isolated in the UK and Australia. We use a mathematical model to assess the importance of the index cases' partnership status in predicting the probability that an introduced XDR NG strain will persist in a population of men who have sex with men (MSM). Methods: We developed an individual-based, anatomical site-specific model of NG transmission in an urban MSM population in Australia. We assume an XDR NG strain is introduced into a population where treatment-sensitive NG is already endemic. We define the index case as the individual initially infected with an introduced XDR NG strain, and their partnership preferences as seeking regular partnerships only, seeking casual partnerships only, or unrestricted. We ran around 1000 simulations for each preference in relation to the index case and recorded the length of time XDR NG persists in the population. Results: In simulations where index cases only have regular partners, XDR NG persists for more than 0.5 years in 37% of simulations. In simulations where index cases only have casual partners, XDR NG persists for more than 0.5 years in 33% of simulations, and in 95% of these the index cases had 5+ casual partners in the past 6 months. In simulations where the index cases have both regular and casual partners, XDR NG persists for more than 0.5 years in 50% of simulations, and in 86% of these the index cases had 5+ casual partners in the past 6 months. Conclusion: Our modelling suggests that an introduced XDR NG is more likely to persist if the index case has a regular partner and is likely to have frequent casual partnerships. These results emphasise the need to identify and treat such individuals and their partners to prevent the initial spread of XDR NG. Disclosure: No significant relationships.